Muzyka w dramatach Tadeusza Micińskiego - Nowak, Iwona (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2012)
The article presents a wealth of musical phenomena in Tadeusz Miciński’s dramas. It attempts to characterize and systematize them on basis of such pieces as Kniaź Patiomkin, Noc rabinowa, W mrokach złotego pałacu, czyli Bazilissa Teofanu or Termopile polskie. Tadeusz Miciński predicted a significant share of the musical element in his dramas. He often precisely indicated, what kind of music should appear in them. The issue of music citations and references given by the Young Poland’s author directly or hidden, requiring identification is the main subject of discussion. Equally important seems to be the question of the function and importance of music in Miciński’s dramas as well as the problem of musical fascination and inspiration in the poet’s writing.